Reliable services in MPLS. - Chen, T.M (IEEE Communications magazine)
MPLS (multiprotocol label switching) is a convergence of various implementations of IP switching using ATM-like ?label swapping? to speed up packet forwarding without changes to existing IP routing protocols. An important practical issue is the capability to recover quickly from faults. We examine distributed methods for fast fault recovery using modified label distribution protocol messages. To maintain and verify service continuity, methods are proposed for traffic and performance monitoring